The feminine tragedy in Madame Bovary by the perspective of psychoanalyzis - Borgato, Rafhael (Lettres Françaises, 2013)
It is this work’s goal to analyze the tragic structure in Flaubert’s novel Madame Bovary considering the perspective of psychoanalyzis – more specifically, analyzing the contradictions between the individual desires and the frame of social life studied by Freud in his work Civilization and its discontents (official English translation). The main subject of this study is about the place occupied by the feminine inside of what Freud comprehend as culture (Western culture) and the similarities of women’s role in the 19th century society and the pattern of the tragic hero (as it is comprehended by German Philosophy since Schelling).